Recommended ESTRO Core Curriculum for Radiation Oncology/Radiotherapy 4th edition. (December 2019) - Benstead, Kim; Lara, Pedro C.; Andreopoulos, Demetrius; Bibault, Jean-Emmanuel; Dix, Anthony; Eller, Yannick G.; Franco, Pierfrancesco; Guiliani, Meredith; Jaal, Jana; Juretic, Antonio; Kozma, Elvisa; Lumsden, Graeme; et al.
Highlights: The ESTRO core curriculum for radiation oncology/radiotherapy has been revised. It is based on CanMEDS 2015 containing 14 entrustable professional activities (EPAs) The manager role has been replaced by the leader role. Proficiency is defined by ranges of EPAs for each tumour site. Abstract: Introduction: In 2017 it was decided to revise the European Core Curriculum for Radiation Oncology/Radiotherapy to produce a 4th edition. The aims of the ESTRO curriculum are to develop comparable standards for training across Europe and to facilitate free movement of specialists across borders. It is also hoped that it will improve the level of training across Europe and will make the non-medical expert roles more explicit. Materials and methods: A wide range of stakeholders including National Society representatives, trainees, recently appointed specialists, members of the European Union Medical Specialists Radiotherapy section, an RTT, a radiobiologist, a physicist and lay members from ESTRO staff developed and commented on iterations of the curriculum. Results: The 4th edition is based on the CanMEDS 2015 framework and identifies 14 Entrustable Professional Activities (EPAs) and the competencies required to perform these. The manager role is replaced by competencies related to leadership. The levels of proficiency required for tumour sites is defined as levels of EPAs. Conclusions: It is hoped that the inclusive method of developing the 4th edition has resulted in a document that will have utility in the wide range of environments in which radiation oncology is practised in Europe.